Retrospective evaluation of oral complications following radiotherapy and chemoradiation in patients with head and neck Cancer - Radhika R. Pai; Ravikiran Ongole; Sourjya Banerjee (Scientific Reports)
Abstract Patients receiving head and neck radiotherapy/chemoradiation may experience a notable and frequent decline in their oral health due to oral complications, including restricted mouth opening, oral mucositis, dry mouth, halitosis, infection, and oral pain. The main aim of this study was to describe the oral complications arising from post-Radiotherapy/chemoradiation among HNC patients through a retrospective survey of 80 patient records. This study collected patients’ comorbid illness and treatment details alongside oral complications. The record review included one-year follow-up details of HNC patients post-completion of radiotherapy/chemoradiation. Among the 80 patients who completed head and neck radiotherapy, 23 experienced interrupted treatment. Among them, most (15%) did not tolerate chemotherapy, which is part of chemoradiation. Thirty-four patients were followed up for oral complications. Most patients experienced symptoms of restricted mouth opening 12(15%), mucositis 6(7.5%), and oral pain 5(6.25%) as oral complications during the subsequent follow-up. Approximately 14 patients reported HNC recurrence. These postradiotherapy/chemoradiation-related oral complications pose a difficult challenge to patients and their caregivers. Awareness of such oral complications will enable healthcare providers to recognize and institute early interventions to provide patients with a better quality of life.